Geophysical exploration of Tural-Rajwadi group of hot springs, West Coast Geothermal Province, Maharashtra, India and its implications. (November 2020) - Low, Upananda; Absar, Ahsan; Duraiswami, Raymond; Singh, Ajay
Highlights: Tural-Rajwadi hot springs from West Coast, India yield low discharge at 50–61°C. They occur within Deccan Trap basalt and have high geothermal gradient (260 °C/km). Isothermal fluid flow in borehole indicates heat transfer by hydrothermal convection. Geophysical studies identify prominent NNW-SSE, NE-SW, and NW-SE lineaments and sub-vertical conduit system for geothermal utilisation. 2D gravity modeling and depth analysis techniques show granitic basement at 770–800 m below ground level. Abstract: Tural-Rajwadi group of hot springs (50−61.5 °C) is located in the southern part of the West Coast Geothermal Province (WCGP) of Maharashtra, India. The hot springs manifest in the basaltic terrain belonging to the Deccan Traps of Cretaceous-Paleocene age (∼65 Ma). To delineate the subsurface structures, a detailed geophysical exploration study has been carried out in the vicinity of the Tural-Rajwadi area for the first time deploying micro-gravity and micro-magnetic surveys in a grid of 1.25 × 4.0 km covering an area of 5 km 2 . The study shows prominent low gravity and low magnetic anomalies demarcating geothermal zones in the study area. Radial average power spectrum analyses of gravity and magnetic data infer seven interfaces of basalt lava flows in the subsurface. Evaluation of geophysical anomaly map reveals that the residual low gravity corroborates with a magnetic low anomaly zone and may indicate an association of a high-temperature gradient at shallow depth in the area. The study shows the presence of several NNW-SSE, NW-SE, NE-SW, and E-W lineaments, which predominantly control the manifestation of hot springs in the area. The distribution of faults, their boundaries, and depth extent have also been determined via derivative analyses, tilt derivative, and Euler's deconvolution methods. Analyses of geophysical data using Werner deconvolution and radial average spectrum methods along two selected profiles indicate the presence of a vertical to sub-vertical conduits system extending to a deeper geothermal source in the study area. In addition, a 2D modeling study of gravity data along a 10 km profile estimates a shallow granite-gneiss basement in the depth range 770−800 m below ground level.